Assessment Indicator from Grandmothers' Support Was the Strongest Correlation to Non-Exclusive Breastfeeding Practice in Young Primiparous Working Mothers - Muladefi Choiriyah; Ziadah Nikmatur Rizqiyah; Setyoadi Setyoadi; Ayut Merdikawati (Journal of Nursing Science Update (JNSU), 2021)
Primiparous mothers will experience various breastfeeding problems because it is the first experience, especially for working mothers. Therefore, they need to get support from their families, mainly from grandmothers. This study aims to analyze the correlation between the grandmother's support and exclusive breastfeeding for primiparous mothers working. This study, conducted in the Arjowinangun Community Health Center coverage area, Malang, used a cross-sectional study approach. The data collection used purposive sampling and questionnaires. One hundred thirty-two respondents had agreed to participate in this study. The results show that most mothers who choose non-exclusive breastfeeding had received insufficient support. There was a significant and strong correlation between grandmother's support and breastfeeding behavior (p-value = 0.000; r = 0.831), which means that the better the grandmother's support, the better exclusive breastfeeding behavior primiparous working mothers. All the support indicators were sufficient categories. The assessment support was the highest correlation to non-exclusive breastfeeding (r = 0.649). The conclusion is grandmother's support has a significant role in the success of exclusive breastfeeding for working mothers, so breastfeeding assistance by health workers should focus on mothers and families, especially grandmothers.